Gestão dos resíduos sólidos urbanos em municípios de pequeno porte: projeto de destinação final adequada para o município de São João do Polêsine-RS - Gabbi, Leandro Nunes (2021)
The management of municipal solid waste has proved to be one of the major challenges for municipal administrations, especially those of small municipalities. Thus, this dissertation had as general objective to develop, in partnership with the municipal administration, a project for environmentally adequate final disposal of municipal solid waste in the municipality of São João do Polêsine-RS, and what problem it presents for this study is: how can a small municipality improve the collection and final disposal of municipal solid waste? Seeking to answer this question, action research was developed with residents of eleven multifamily condominiums located in the urban area of the headquarters of the municipality of São João do Polêsine-RS. The action research was the development of a pilot project with the objective of verifying the possible barriers and facilitators that can be presented to managers of a small municipality during the process of implementation of selective collection and environmentally appropriate final disposal of municipal solid waste. For this, we used the application of questionnaires, collections, separation and weighing of municipal solid waste, as forms of diagnosis and evaluation, and information and awareness campaigns, in addition to the installation of standardized bins and identified as ways to encourage the participation of the target public in selective collection actions. During the development of the pilot project, 70.89% of the waste that can be reused (organic and dry recyclable) was reused, and 47.54% of the total mass of municipal solid waste generated by the target public stopped going to the landfill. Also, as a result, the municipal administration of São João do Polêsine-RS was presented to the municipal administration of São João do Polêsine-RS a set of actions to be developed aiming at the implementation of selective collection for other citizens, thus improving the environmentally adequate final destination of waste generated in the municipality. As a product of this work, a "Guide for the implementation of selective collection in small municipalities" was elaborated, which can serve as a support tool for municipal managers of any municipality characterized as such.